SAT0657 Can vascular inflammation in ra be detected using contrast enhanced mri? preliminary results. (15th June 2017) - Skeoch, S; Little, R; Watson, Y; Cheung, S; O'Connor, J; Alexander, Y; Bruce, I; Parker, G; Waterton, J
Abstract : Background: In rheumatoid arthritis (RA) vascular inflammation may contribute to excess cardiovascular (CV) risk. Contrast enhanced MRI has been used to detect vascular inflammation in Takayasu's arteritis. In RA, its utility has not been studied but it may provide a method of identifying and monitoring vascular inflammation and effects of therapy. Objectives: We sought to compare carotid artery wall enhancement on contrast enhanced MRI in RA patients and controls and evaluate association with circulating markers of inflammation, endothelial activation and CV risk factors. Methods: Patients and age/sex matched controls underwent clinical and serological assessment (details in Table 1 ) and a screening carotid ultrasound. Those with wall thickening>2mm had a carotid MRI. T1 -weighted images were acquired before and after gadopentate injection on a 3T scanner. Increase in mean signal intensity (SI) in the carotid vessel wall normalised to adjacent skeletal muscle provided a global enhancement metric (WEG ). Histograms of distribution of SIs on pre-and post- contrast images were generated and bimodal Gaussian distributions fitted to explore patterns of enhancement within the wall. MRI measurements were compared between groups and association with serological markers tested using non-parametric statistics. Results: 27 patients and 10 controls underwent MR imaging. Key characteristics are seen in Table 1 . There was no difference in WEG between groups and no association with serological markers. However a bimodal distribution of SI in vessel wall was observed (Figure 1 ) and in exploratory analysis these two components were analysed separately. For the low-signal component enhancement (WElow ) correlated with ESR, I-CAM, e-selectin (r=0.39, p=0.03;r=0.44, p=0.01;r=0.37, p=0.04). There was a trend towards correlation with CRP (r=0.30, 0.08) and towards higher values in patients (median 0.20 (0.15, 0.33) vs 0.14 (0.11, 0.22), p=0.051). Enhancement in the high-signal component (WEhigh ) was not associated with serological markers or RA status. Conclusions: Simple global SI measurement on MRI did not suggest vascular inflammation in RA. However, the bimodal SI distribution may represent different wall components e.g. intima and adventitia. The differential enhancement, and association of WElow with inflammation, endothelial activation and RA status, warrants further investigation. Disclosure of Interest: None declared